Implementing the Morning Jarimatika Game as a Finger-Based Numeracy Strategy: A Study at SD 77 Penerokan - Ketrin Rinayanti Manullang; Fauziah Anwar (Gateway for Understanding Research in Education, 2026)
This study investigates the effectiveness of the Morning Jarimatika Game as a finger-based instructional strategy to improve elementary students’ numeracy skills. Numeracy is essential for solving everyday mathematical problems; however, the structured use of Jarimatika as a daily learning activity remains underexplored, which highlights the novelty of this study. A quantitative approach with a one-group pretest–posttest design was employed, involving 25 students at SD 77 Penerokan. Data were analyzed using descriptive and inferential statistics, including normality, homogeneity, and t-tests, as well as N-gain and effect size calculations. The results show a significant improvement in numeracy skills, with mean scores increasing from 63.20 to 86.00. The data were normally distributed and homogeneous, and the t-test indicated a significant difference (Sig. < 0.001). The effect size was large (Cohen’s d = 2.752), with a moderate N-gain (62.27%). These findings suggest that the Morning Jarimatika Game is an effective numeracy-based instructional strategy that can be applied as a classroom warm-up activity. Future research should include control groups, larger samples, and long-term implementation across diverse educational contexts.